2022
DOI: 10.3389/fenvs.2021.793221
|View full text |Cite
|
Sign up to set email alerts
|

Financial Inclusion and Carbon Reduction: Evidence From Chinese Counties

Abstract: With the improvement of inclusive financial system, China’s economy has made significant development and growth. It worth in-depth investigation on environmental impact of financial inclusion, since growing GDP usually accompanied by more intensive carbon emission. This paper aims to reveal whether financial inclusion contributes to the carbon reduction in China using county-level dataset. A fixed-effect panel regression approach is adopted to examine the impact of financial inclusion on county-level regional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…This finding agrees with that of Acheampong (2019) and Iorember et al (2020). Conversely, the works of Jiakui et al (2023) and Yang et al (2022) point to the reduced impact of FD on carbon emissions. Conversely, HC remains negative and significant at the 5% level, both in the short and long run.…”
Section: Estimates Of the Augmented C-s Ardlsupporting
confidence: 90%
See 2 more Smart Citations
“…This finding agrees with that of Acheampong (2019) and Iorember et al (2020). Conversely, the works of Jiakui et al (2023) and Yang et al (2022) point to the reduced impact of FD on carbon emissions. Conversely, HC remains negative and significant at the 5% level, both in the short and long run.…”
Section: Estimates Of the Augmented C-s Ardlsupporting
confidence: 90%
“…Earlier, although Frankel and Romer (1999) had identified foreign direct investment as a crucial channel of financialization to growth, Haber et al (2020) rather considered the stock and equities market as the two prominent channels of this transmission process. Yet another strand of scholars found that financialization rather reduces the rate of CO 2 emissions (Jiakui et al, 2023; Sheraz et al, 2021; Yang et al, 2022). Such studies appear to provide empirical evidence that given its potential moderating role, expansion in financial access and financial infrastructure would facilitate the procurement of renewable or cleaner energy production technologies, which may in turn reduce CO 2 emission.…”
Section: Review Of Related Empirical Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Using an econometric model, Chen et al (2020) show that political globalization reduces CO 2 emissions, and You and Lv (2018) report that economic globalization has a significant negative impact. Farouq et al (2021) argue that financial globalization uncertainty is inversely related to CO 2 emissions, and enhancing the financial market can reduce carbon emissions by improving carbon sequestration capacity and industrial structure (Yang et al, 2022). Many scholars evaluate the environmental Kuznets curve hypothesis by analyzing whether there is an inverted U-shaped relationship between economic growth and carbon emissions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Using number of ATMs and insurance policy as a key interest variable and employing the ARDL model study found that an increase in number of ATMs and total insurance enhances the renewable energy consumption and CO 2 emission in China province. Consequently, using the country-level data set of China Yang et al (2022) explored the relationship between financial inclusion and carbon emission. Using panel data Carbon emissions in India methodology, study explored the negative association between financial inclusion and regional level carbon emission in China.…”
Section: Key Literaturementioning
confidence: 99%